The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.25260/ea.17.27.2.0.416
|View full text |Cite
|
Sign up to set email alerts
|

Factores que afectan el tamaño del ámbito hogareño de felinos (Mammalia, Carnívora), con énfasis en tres especies americanas

Abstract: ABSTRACT. We evaluated several factors that might be related to the home-range size of felids at both inter and intraspecific levels. At the interspecific level, we tested the influence of body mass on home range size of 19 felid species, while controlling for phylogeny. At the species level, we evaluated the effect of sex and habitat type (open vs. closed) on the home range size of three species of felids occurring in America, Panthera onca, Leopardus pardalis and Puma concolor, which are among the most studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…While using home range size is ideal in representing overall mobility over an extended period, it may not be ideal in parsing out differences in actual loading from terrestrial locomotion. Moreover, home range sizes can vary significantly (see Methods section for ranges for these species) depending on Femur/humerus BVF Femur/tibia BVF Humerus/tibia BVF resource availability and season (Grigione et al, 2002;Machado et al, 2017). For this reason, we also included a prediction using daily travel distance.…”
Section: Resultsmentioning
confidence: 99%
“…While using home range size is ideal in representing overall mobility over an extended period, it may not be ideal in parsing out differences in actual loading from terrestrial locomotion. Moreover, home range sizes can vary significantly (see Methods section for ranges for these species) depending on Femur/humerus BVF Femur/tibia BVF Humerus/tibia BVF resource availability and season (Grigione et al, 2002;Machado et al, 2017). For this reason, we also included a prediction using daily travel distance.…”
Section: Resultsmentioning
confidence: 99%
“…Although other large carnivores, such as Sumatran tigers and bears, were also found, they were excluded from the study's analysis. Since felids are hypercarnivores (Sunquist and Sunquist 2002) and require a significant amount of habitat for foraging to find prey (Machado et al 2017), this may be the reason why felids, except for P. bengalensis, were not found in patch A, the smallest forest patch.…”
Section: Discussionmentioning
confidence: 99%
“…Reported home range sizes vary from 0.9 to 17 km 2 [ 14 , 52 ]. Though research on these species has shown high variation in home range sizes, it is highly dependent on habitat and prey availability [ 22 , 54 ]. In a previous study on ocelot space use in the Madidi area, Ayala and Viscarra [ 35 ] found particularly high densities, with smaller than average home ranges.…”
Section: Methodsmentioning
confidence: 99%